THE USE OF AUTHENTIC VIDEO MATERIALS FOR THE FORMATION OF PROJECT ACTIVITY SKILLS IN ENGLISH LESSONS IN SCHOOLS - Olimova Muslima Ulug'bek qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The article discusses the possibility of using authentic video materials for the formation of project activity skills in English lessons in schools. The classification and requirements for the method of projects are revealed. The possibility of using video materials for the development of listening skills and stepby-step work with them is also being explored.